2006
DOI: 10.1002/crat.200510541
|View full text |Cite
|
Sign up to set email alerts
|

MOVPE growth of GaAs on Ge substrates by inserting a thin low temperature buffer layer

Abstract: High quality GaAs layers have been grown by low pressure MOVPE on Ge(001) and Ge(001) 9° off oriented in [110] direction by using a thin low temperature (LT) GaAs layer. Investigations of the initial growth step were performed at different V/III ratios and temperatures. To show the good buffer layer quality solar cell structures were grown on off oriented n-Ge(001) and n-GaAs(001) substrates. The surface morphology was studied by atomic force microscopy which showed the step-flow growth mode on 1.2 µm thick G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“…1 68 nm, respectively, which suggests that the GaAs films with AlAs/GaAs PALE interlayer could get smoother surface morphology than those growth without interlayer and with AlGa/AlGaAs PALE interlayer. Compared with RMS roughnesses of 12.47 nm and 1.5 nm in 10 lm  10 lm scan area reported by Hudait et al [13] and Scholz et al [14], significant improvement in surface root-mean-square (RMS) roughness of GaAs epilayers grown on 9°offcut Ge substrate has been obtained in our work. The cross sectional transmission electron microscope (XTEM) is employed to further study the microstructures of all these samples.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…1 68 nm, respectively, which suggests that the GaAs films with AlAs/GaAs PALE interlayer could get smoother surface morphology than those growth without interlayer and with AlGa/AlGaAs PALE interlayer. Compared with RMS roughnesses of 12.47 nm and 1.5 nm in 10 lm  10 lm scan area reported by Hudait et al [13] and Scholz et al [14], significant improvement in surface root-mean-square (RMS) roughness of GaAs epilayers grown on 9°offcut Ge substrate has been obtained in our work. The cross sectional transmission electron microscope (XTEM) is employed to further study the microstructures of all these samples.…”
Section: Methodssupporting
confidence: 71%
“…Even though the mismatches of lattice constants and thermal expansion coefficients between GaAs and Ge are negligible, challenges remain in growing GaAs directly on Ge substrate [2], mainly due to the formation of anti-phase domains (APDs) when polar materials GaAs grown on nonpolar materials Ge [5,6], and the atomic interdiffusion near the GaAs/Ge interface [1,[7][8][9]. For the former, it has been well established that under proper growth conditions, the APDs can be eliminated by the adoption of off-cut Ge substrates [10][11][12][13][14][15]. For the later, Chia et al demonstrated that the interdiffusion could be effectively blocked by introducing an interlayer with high bonding energy such as Al x Ga 1Àx As [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The best results in FWHM of GaAs films are observed when they are grown on the Ge or GOI wafers (Geon-Insulator, -Ge on Si by bonding, for more details on such platform see Chapter 3). Thus, the FWHM values of GaAs/Ge and GaAs/GOI borrowed from Scholtz et al [37] and Loubyshev et al [38] are hit on or near of the theoretical dependence (Fig. 2).…”
Section: Direct Gaas-on-si Epitaxymentioning
confidence: 70%
“…Two temperature ranges have been reported for the GaAs buffer layer that allows for the growth of APB-free GaAs layers. One is in the [350-550°C] range [4,[14][15][16][17] and the second one is in the [600-725°C range] [7,[17][18][19][20]. Between these two temperature ranges, growth of a mixed distribution of GaAs domains occurs, leading to the formation of numerous APB [17].…”
Section: Introductionmentioning
confidence: 99%